2007
DOI: 10.1128/jvi.02655-06
|View full text |Cite
|
Sign up to set email alerts
|

The Glycoprotein Cytoplasmic Tail of Uukuniemi Virus ( Bunyaviridae ) Interacts with Ribonucleoproteins and Is Critical for Genome Packaging

Abstract: We have analyzed the importance of specific amino acids in the cytoplasmic tail of the glycoprotein G N for packaging of ribonucleoproteins (RNPs) into virus-like particles (VLPs) of Uukuniemi virus (UUK virus), a member of the Bunyaviridae family. In order to study packaging, we added the G N /G C glycoprotein precursor (p110) to a polymerase I-driven minigenome rescue system to generate VLPs that are released into the supernatant. These particles can infect new cells, and reporter gene expression can be dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 48 publications
5
79
0
Order By: Relevance
“…Based on this observation, it was suggested that the cytoplasmic tails of the viral glycoproteins might bind the viral ribonucleoprotein (6). Indeed, recent results have shown that the G1 tail binds the viral ribonucleoprotein in phlebovirus (7) and is required for packaging the genome in orthobunyavirus (8). These data suggest that the G1 tail plays a critical role in viral assembly.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Based on this observation, it was suggested that the cytoplasmic tails of the viral glycoproteins might bind the viral ribonucleoprotein (6). Indeed, recent results have shown that the G1 tail binds the viral ribonucleoprotein in phlebovirus (7) and is required for packaging the genome in orthobunyavirus (8). These data suggest that the G1 tail plays a critical role in viral assembly.…”
mentioning
confidence: 77%
“…The G1 tail of Bunyaviriade viruses is important in viral assembly (7,8) and host-pathogen interaction (9 -13). Our results showed that a conserved cysteine/histidinerich region in the hantavirus G1 tail (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Like the polymerase, which catalyses RNA replication and transcription by cap-snatching (6), NP is multifunctional. In coating exclusively genomic or antigenomic viral RNA (but not viral mRNA or cellular RNA), it protects the viral genome from degradation, avoids formation of dsRNA between viral RNAs of opposite polarity, compacts the RNA into RNPs, and by interacting with the glycoprotein tails inside the virion membrane, actively promotes packaging into progeny virions (7,8). Dynamic interactions of NP with the polymerase are also critical, allowing the polymerase controlled access to the RNA within template RNPs on the one hand and nucleating assembly of progeny RNPs only when the polymerase is functioning as a replicase.…”
mentioning
confidence: 99%
“…RVFV N is thought to interact with the viral RdRp because N is essential to replication and transcription (4). N also plays a role in virus assembly through interactions with the viral envelope glycoproteins (G N and G C ) (5).…”
mentioning
confidence: 99%